Bots Coordinating Work in Open Source Software Projects. - Hukal, Philipp; Berente, Nicholas; Germonprez, Matt; Schecter, Aaron (Computer (00189162), 2019)
Increasingly, bots are being used to coordinate work in open source software projects. As mechanisms that ensure the smooth functioning of open source software projects, bot activity influences how scholars and practitioners understand open source software development.